Relationship between Negative Mindset and English-Speaking Anxiety in English Students - Lusia Ayuni Andi; Juliana M. Y. Benu; Marleny P. Panis (Universitas Nusa Cendana, 2022)
The ability to speak English is the main priority of many languages ​​being studied, inadequate mastery of English is often a source of anxiety experienced by students. English anxiety is anxiety that arises as perceptions, beliefs, feelings, and attitudes that arise in individuals in learning and using English. English anxiety is a result of affective factors that arise due to several things: lack of knowledge of English, lack of preparation, fear of making mistakes, and difficulty understanding instructions from the teacher. The hypothesis in this study is that there is a relationship between negative thought patterns and English speaking anxiety in students majoring in English at UNWIRA Kupang. Participants in this study were students majoring in English with a total of 130 respondents. The analysis in this study uses correlational analysis. The results of the analysis show that there is a correlation coefficient between negative thinking patterns and English-speaking anxiety of 0.434 with a significant value of 0.000 <0.05.